The effect of Felder's reflective active-based vak learning style on early childhood science learning outcomes - Safarina, Arfani Rahma; Taufiqulloh, Taufiqulloh; Agung N, Rahmad (Universitas Pahlawan Tuanku Tambusai, 2025)
The phenomenon that occurred in the field at the research location, namely at Aisyiyah Bustanul Athfal I Kindergarten and Aisyiyah Bustanul Athfal XI Kindergarten, East Tegal District, Tegal City, learning shows that science learning also supports the development of social and emotional skills. The purpose of this study is to determine visual, auditory, and kinesthetic learning styles, both active and reflective, on early childhood science learning outcomes. This type of research uses Mixed Methods research (Quantitative and Qualitative Combination). The data collection technique in this mixed methods research collects data through: Interviews, Observations, Documentation, Questionnaires, Test Methods. The data analysis technique in this study uses Sequential Explanatory. The results of this study show that there is a significant influence between visual, auditory, and kinesthetic learning style variables, both active and reflective, on early childhood science learning outcomes.